Automated detection of vehicles license plate using image processing techniques - Farhana Ahmad Poad; Noor Shuraya Othman; Roshayati Yahya Atan; Jusrorizal Fadly Jusoh; Mumtaz Anwar Hussin (Institute of Advanced Engineering and Science, 2020)
The aim of this project is to design an Automated Detection of License Plate (ADLP) system based on image processing techniques. There are two techniques that are commonly used in detecting the target, which are the Optical Character Recognition (OCR) and the split and merge segmentation. Basically, the OCR technique performs the operation using individual character of the license plate with alphanumeri characteristic. While, the split and merge segmentation technique split the image of captured plate into a region of interest. These two techniques are utilized and implemented using MATLAB software and the performance of detection is tested on the image and a comparison is done between both techniques. The results show that both techniques can perform well for license plate with some error.